Selecting representative products for quantifying environmental impacts of consumption in urban areas. (20th September 2017) - Lavers, Alexandra; Kalmykova, Yuliya; Rosado, Leonardo; Oliveira, Felipe; Laurenti, Rafael
Abstract: Populations are becoming more urban than rural, creating concentrated areas with high consumption of products. Understanding and influencing the environmental impact of consumption within cities becomes therefore increasingly important. Although there have been several studies evaluating the environmental impact of consumption at the global, national, and regional scale, there are few methods currently available to estimate impact at the urban level. There is therefore a need for a systematic approach to select appropriate, region-specific representative products. This study combines material flow analysis with life cycle assessment to select representative products that can be used as proxies to assess the environmental impact of urban areas using life cycle impact factors. The selection was based on the following criteria: the top consumed products within a product category, consistent products with respect to time and geography, and product types with known high environmental impact. The representative products were identified for three Swedish cities: Stockholm, Gothenburg and Malmo, using sixteen years of annual urban-level material flow analysis data (1996–2011). A total of 71 products across 44 categories, were identified as representative of the 10, 000 product types consumed in the urban areas analyzed. The method described in this study can be used by practitioners to identify representative products in any urban area with material flow data and allows for a more comprehensive and tailored analysis that what has been previously available. Highlights: Method for product-level MFA with LCA integration to quantify environmental impact. A systematic method applicable to different regions and countries is proposed. 10, 000 products can be reduced to 71 representative products. Enables detailed evaluation of environmental impact of region-specific consumption.